Radiative GRMHD simulations of accretion disks. Issue 9 (26th December 2017) - Kluźniak, W.; Abarca, D.; Mishra, B.
Abstract : We describe some recent results on the evolution of accretion disks around black holes and neutron stars obtained in magnetohydrodynamic (MHD) simulations in general relativity (GR) with the inclusion of radiation (GRRMHD).